City enhancement beyond the notion of “sustainable city”: introduction to integrated assessment for city enhancement (iACE) toolkit - Cheshmehzangi, Ali (Elsevier, 2016)
Over the course of past three decades, many researchers questioned the oxymoron characteristics of sustainable city. It is, therefore, uncertain that to what extend cities can actually be sustainable or are they sustainable at all. This study challenges the notion of “Sustainable City” and instead proposes for pathways towards city enhancement strategies, such as energy optimisation and low carbon development. As a result, the study introduces a holistic toolkit that is aimed to enhance the city's efficiency and optimise its performance.